Assessing adherence to physical activity programs post-stroke at home: A systematic review of randomized controlled trials. Issue 3 (3rd April 2021) - Lu, Richard; Lloyd-Randolfi, Dominic; Jones, Heather; Connor, Lisa Tabor; AlHeresh, Rawan
ABSTRACT: Background: Physical activity at home provides significant benefits post-stroke. Adherence assessments contribute to objective evaluation of treatment effectiveness across settings. Objectives: The aims of this study were to (1) conduct a systematic review with focus on analyzing the reporting quality of RCTs that incorporate home physical activity interventions among people post-stroke, and utilize a physical activity adherence assessment and to: (2) identify, group, and critically appraise physical activity adherence assessments within the identified studies. Methods: A literature search for RCTs was conducted. Articles needed to (1) study adult, post-stroke participants, (2) include a physical activity intervention at home, (3) utilize a physical activity adherence assessment, (4) be published in English in a peer reviewed journal. Two independent reviewers assessed the reporting quality of each RCT for conformity to 39 Consolidated Standards of Reporting Trials (CONSORT) items, followed by an evaluation of adherence assessment methods. Results: Eleven studies met the inclusion criteria and none of them reported all CONSORT items. The median number of "fully reported" items was 7 out of 39. Ten of the 11 RCTs employed the adherence diary as an assessment method. The adherence parameters of frequency and duration were applied with greater frequency than intensity and accuracy. No evidence of an objective method of adherence assessment was found. Conclusions: This systematic review revealed suboptimal reporting of RCTs of physical activity interventions. The use of a diary with the post-stroke population at home was common, despite the lack of an objective method of adherence assessment. Stricter compliance to CONSORT guidelines and complementary direct adherence measurement is advised to improve activity adherence research.